Development of a Sexual Dysfunction Scale for Women With Inflammatory Bowel Disease. Issue 11 (22nd June 2018) - de Silva, Punyanganie S; O'Toole, Aoibhlinn; Marc, Linda G; Ulysse, Christine A; Testa, Marcia A; Julsgaard, Mette; Ngyuen, Deanna; Ananthakrishnan, Ashwin; Laursen, Tine; Højgaard, Astrid; Christensen, Lisbet A; Korzenik, Joshua; et al.
Abstract: Background: Women with inflammatory bowel disease (IBD) may have decreased sexual function. To understand how common this condition is in our female patients, we developed a new IBD-specific Female Sexual Dysfunction Scale (the IBD-FSDS). Methods: We performed a prospective cross-sectional study of 454 female IBD patients ≥18 years of age attending 1 of 3 IBD clinics in the United States or Denmark. We gathered information on sexual function via a de novo 23-item scale. General sexual functioning was measured with the Female Sexual Function Index (FSFI) and the Female Sexual Distress Scale–Revised (FSDS-R). Depressive symptoms were measured with the Patient Health Questionnaire–9 (PHQ-9). Medical history and sociodemographic data were collected via chart review. Exploratory factor analyses (EFAs) of the English language version of IBD-FSDS assessed unidimensionality, factor structure, reliability, criterion validity, and construct validity. Results: EFAs suggested retaining 15-items creating a unidimensional scale with strong internal consistency reliability (α = 0.93). Validity of the English language IBD-FSDS was measured using Spearman's coefficient, demonstrating significant criterion validity with the FSDS-R ( P < 0.05) and the FSFI ( P < 0.05) and significant construct validity with the composite for cases of active IBD ( P < 0.05) and PHQ-9 ( P < 0.05). Sexual dysfunction in women with IBD was significantly associated with depression ( P = 0.042), active IBD ( P = 0.002), and no history of surgery ( P = 0.044). Conclusions: We have developed and validated an IBD-specific scale to assess the psychosexual impact of IBD in women. This novel screening questionnaire may help health care providers recognize factors contributing to impaired sexual function in their female patients.